Factors influencing eating behavior of Benghazi University students - El-Mani, Souad Farag; Mansour, Reima M.; Abdessamad, Amna E; Al-Abbar, Etchomaly A.; Shallouf, Nour; Amer, Randa (Asian Journal of Medical Sciences, 2020)
Background: University students are more exposed to new individual and environmental influences. This transition period is considered as a risky life phase because it’s characterized by changing in physical and social status as well as changing in the lifestyle that will affect the eating behavior of students. Aims and Objectives: The current study aimed to determine the factors influencing the eating behaviors of Benghazi University students. Materials and Methods: A cross sectional study was undertaken for a period from January to May 2019 in Benghazi University. Samples of 300 students were requested to fill out a questionnaire. SPSS was used to analyze the data. Results: After starting university, (64%) of students stated that they had a change in eating behavior and (59%) of participants reported unhealthy eating pattern. About (67%) of students had a sedentary lifestyle with the majority of them were having unhealthy eating patterns (P value = 0.000). According to the BMI the majority of students had normal weight (62.6%). About (80%) of student reported that the lack of time to prepare a healthy meal during study period was effective and More than half of the students reported that inaccessibility of healthy food, student’s positive emotions, poor knowledge of healthy food, and stress associated with exams period were effective. There was a statistical difference between student’s eating patterns and poor knowledge, lack of time, stress, body weight concerns, negative emotions, peer pressure, lack of parental control, mass media and social life (P value < 0.05). Conclusion: This study concluded that the majority of students undergo a negative shift in their eating and lifestyle after starting university, and there is statistical difference between many factors and student’s eating pattern.